On Anisotropic $BV$-Spaces - P. Kogut (Researches in Mathematics)
This paper is devoted to the study of a new class of functional spaces, the so-called anisotropic $BV$-spaces with a degenerate weight. We give a precise definition of such spaces and show that they can be viewed as a natural generalization of the standard space of functions with bounded variation.